2014
DOI: 10.1007/s11695-014-1233-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on Male Obesity-Associated Secondary Hypogonadism: Comparison of Laparoscopic Gastric Bypass with Restrictive Procedures

Abstract: Bariatric surgery results in the complete resolution of male obesity-associated secondary hypogonadism (MOSH) in many patients. However, the effects of different bariatric surgical procedures on male sexual hormone profiles and sexual dysfunction have not been compared to date. We compared the pre- and post-operative (at least 6 months after initial surgery) sex hormone profiles of 20 severely obese men submitted to laparoscopic gastric bypass (LGB) with 15 similar patients submitted to restrictive techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…In contrast to conservative interventions, bariatric surgery is reported as a very effective means of achieving significant and sustained weight loss in severely patients with obesity. In addition, observational data derived from several studies showed that bariatric surgery is also very effective in increasing testosterone levels and recovering the HPT axis function . Interestingly, hypogonadal men were reported to lose more weight than eugonadal men when submitted to bariatric surgery .…”
Section: Male Hypogonadism and Obesity: Breaking The Vicious Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to conservative interventions, bariatric surgery is reported as a very effective means of achieving significant and sustained weight loss in severely patients with obesity. In addition, observational data derived from several studies showed that bariatric surgery is also very effective in increasing testosterone levels and recovering the HPT axis function . Interestingly, hypogonadal men were reported to lose more weight than eugonadal men when submitted to bariatric surgery .…”
Section: Male Hypogonadism and Obesity: Breaking The Vicious Cyclementioning
confidence: 99%
“…In addition, observational data derived from several studies showed that bariatric surgery is also very effective in increasing testosterone levels and recovering the HPT axis function. 89,133 Interestingly, hypogonadal men were reported to lose more weight than eugonadal men when submitted to bariatric surgery. 134 Thus, it is hypothesized that the weight loss reverts the vicious cycle, as allows the recovery of testosterone to physiological levels, while in turn increased testosterone decreases weight gain due to its inhibitory effects on adipocytes differentiation and lipid uptake and ultimately allowing to recover the metabolic balance.…”
Section: Male Hypogonadism and Obesity: Consequences For Male Fertimentioning
confidence: 99%
“…PCOS and MOSH have been found in approximately 50% and 60% of severely obese female and male patients submitted to bariatric surgical procedures (Escobar‐Morreale et al ., ; Calderon et al ., ). Of note, the marked weight loss that occurs after bariatric surgery results into remission of the hormonal derangements present in PCOS (Escobar‐Morreale et al ., ) and MOSH (Botella‐Carretero et al ., ; Calderon et al ., ; Samavat et al ., ) in almost all patients.…”
Section: Introductionmentioning
confidence: 97%
“…PCOS and MOSH have been found in approximately 50% and 60% of severely obese female and male patients submitted to bariatric surgical procedures (Escobar‐Morreale et al ., ; Calderon et al ., ). Of note, the marked weight loss that occurs after bariatric surgery results into remission of the hormonal derangements present in PCOS (Escobar‐Morreale et al ., ) and MOSH (Botella‐Carretero et al ., ; Calderon et al ., ; Samavat et al ., ) in almost all patients. The latter has been confirmed by a recent meta‐analysis showing that bariatric surgery induces an increase in both total testosterone (TT) and free testosterone (FT), the normalization of serum sex hormone‐binding globulin (SHBG), and the remission of MOSH in a large proportion of patients (Corona et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, obesity-associated gonadal dysfunction consists of hyperandrogenism in women (2) but hypogonadism in men (3). proliferation is influenced by the balance of sex hormones in healthy men and women (4).…”
Section: Introductionmentioning
confidence: 99%